Maternal melatonin levels and temporal dietary intake: results from MY-CARE cohort study - Ai Ni Teoh; Satvinder Kaur; Siti Raihanah Shafie; Nurul Husna Mohd Shukri; Normina Ahmad Bustami; Masaki Takahashi; Shigenobu Shibata (BMC, 2023)
Abstract Chrononutrition emerges as a novel approach to promote circadian alignment and metabolic health by means of time-of-the-day dietary intake. However, the relationship between maternal circadian rhythm and temporal dietary intake during pregnancy remains understudied. This study aimed to determine the change in melatonin levels in pregnant women across gestation and its association with temporal energy and macronutrient intake. This was a prospective cohort involving 70 healthy primigravidas. During the second and third trimesters, pregnant women provided salivary samples collected at 9:00, 15:00, 21:00, and 3:00 h over a 24 h day for melatonin assay. Data on chrononutrition characteristics were collected using a 3-day food record. Parameters derived from melatonin measurements including mean, amplitude, maximal level, area under the curve with respect to increase (AUCI), and area under the curve with respect to ground (AUCG) were computed. A rhythmic melatonin secretion over the day that remained stable across trimesters was observed among the pregnant women. There was no significant elevation in salivary melatonin levels as pregnancy advanced. In the second trimester, higher energy intake during 12:00-15:59 h and 19:00-06:59 h predicted a steeper melatonin AUCI (β=-0.32, p = 0.034) and higher AUCG (β = 0.26, p = 0.042), respectively. Macronutrient intake within 12:00-15:59 h was negatively associated with mean melatonin (Fat: β=-0.28, p = 0.041) and AUCG (Carbohydrate: β=-0.37, p = 0.003; Protein: β=-0.27, p = 0.036; Fat: β=-0.32, p = 0.014). As pregnant women progressed from the second to the third trimester, a flatter AUCI was associated with a reduced carbohydrate intake during 12:00-15:59 h (β=-0.40, p = 0.026). No significant association was detected during the third trimester. Our findings show that higher energy and macronutrient intakes particularly during 12:00-15:59 h and 19:00-06:59 h are associated with the disparities in maternal melatonin levels. Findings suggest the potential of time-based dietary approaches to entrain circadian rhythm in pregnant women.